Novel AIE-active tetraphenylethylene derivatives as multitask smart materials for turn-on mechanofluorochromism, quantitative sensing of pressure and picric acid detection. (July 2022) - Zhang, Gaobin; Zhang, Shuaishuai; Chen, Fangjie; Ni, Yingyong; Wang, Chengyuan; Yang, Longmei; Kong, Lin; Yang, Jiaxiang
Abstract: Developing multitask smart materials is in high demand and remains challenging in the organic fluorophore research field. In this work, we designed and synthesized a series of tetraphenylethylene modified fluorophores (TPEN, TPEH, TPEF, TPEIZ, TPECN ) with D-π-A configuration and various terminal substituents, whose packing structures in the solid state were finely manipulated and revealed by single-crystal structure analysis. These materials showed excellent aggregation-induced emission (AIE) and mechanofluorochromism (MFC) properties. The fluorescence peaks of TPEH, TPEF, TPEIZ and TPECN were gradually red-shifted with the change of solid fluorescence quantum yields ( Φ F ) under grinding, derived by the different molecular conformation and packing between crystalline and amorphous states. Notably, thanks to the high sensitivity to force, TPEH and TPEF exhibited high-contrast turn-on MFC property with obviously increase of Φ F . Meanwhile, TPEF achieved the quantitative detection of pressure in turn-on modal due to the special molecular packing induced by the F atom. Additionally, TPEH, TPEF, TPEIZ and TPECN were applied for the detection of picric acid (PA) and the limit of detection for the four materials was 7.58 μM, 458 nM, 634 nM and 4.62 μM, respectively. The mechanism was attributed to the synergistic effects of coulombic forces and protonation/hydrogen bonding interactions and the photoinduced electron transfer (PET) process. This work provides a new scope for rational design of highly sensitive multitask smart materials for low-pressure and PA detection. Highlights: A series of tetraphenylethylene modified D-π-A fluorophores were designed and synthesized. The compounds showed excellent aggregation-induced emission (AIE) and mechanofluorochromism (MFC) properties. TPEF exhibited high-contrast turn-on MFC property and quantitative detection of pressure in turn-on modal. The materials were applied for the detection of picric acid (PA) with low limit of detection.